Gambaran Quality of Life Peserta Program Pengelolaan Penyakit Kronis - Mu'thiya Hasymah; Madyo Maryoto; Ita Apriliyani (JURNAL KEPERAWATAN MERSI, 2025)
Background: The increasing number of elderly in Indonesia has an impact on the increasing  prevalence of chronic diseases, especially hypertension and diabetes mellitus, which has implications for reducing Quality of Life. The Chronic Disease Management Program (Prolanis) organized by BPJS Kesehatan aims to maintain the health condition of participants to avoid complications and improve Quality of Life. Objective: This study aims to determine the description of Quality of Life of Prolanis participants at the Kutawis Community Health Center, Purbalingga. Methods: This study used a quantitative descriptive design with a cross-sectional approach. The research sample was 49 respondents from 93 Prolanis participants selected using an accidental sampling technique. The research instrument used the WHOQOL-BREF questionnaire that assesses quality of life in four domains, namely physical, psychological, social, and environmental. Results: The results showed that the quality of life of Prolanis participants was generally in the moderate category (49%). Based on the domain, most respondents had a moderate quality of life category, namely physical (75.5%), psychological (85.7%), social (71.4%), and environmental (83.7%). Conclusion: It can be concluded that the quality of life of Prolanis participants at the Kutawis Community Health Center in Purbalingga is mostly in the moderate category across all four domains. Therefore, although Prolanis plays a role in maintaining quality of life, further intervention and evaluation are needed to improve participants' quality of life to the high category.